Disordered magnetism in superconducting KFe2As2 single crystals. Issue 3 (18th January 2013) - Grinenko, V.; Drechsler, S.‐L.; Abdel‐Hafiez, M.; Aswartham, S.; Wolter, A. U. B.; Wurmehl, S.; Hess, C.; Nenkov, K.; Fuchs, G.; Efremov, D. V.; Holzapfel, B.; van den Brink, J.; et al.
Abstract High‐quality KFe2As2 (K122) single crystals synthesized by different techniques have been studied by magnetization and specific heat (SH) measurements. The adopted phenomenological analysis of the normal state properties shows that there are two types of samples both affected by disordered magnetic phases: (i) cluster‐glass (CG) like or (ii) Griffiths phase (G) like. For (i) at low applied magnetic fields the T‐dependence of the zero‐field‐cooled (ZFC) linear susceptibility χl exhibits an anomaly with an irreversible behavior in ZFC and field‐cooled (FC) data. This anomaly is related to the freezing temperature Tf of a CG. For the investigated samples the extrapolated Tf to B = 0 varies between 56 and 90 K. Below Tf we observed a magnetic hysteresis in the field dependence of the isothermal magnetization M(B). The frequency shift of the freezing temperature <![CDATA[$\delta T_{{\rm f}} = {\rm \Delta }T_{{\rm f}} /[T_{{\rm f}} {\rm \Delta }({\rm ln}\, \nu )]\sim 0.05$]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t15q" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> has an intermediate value, which provides evidence for the formation of a CG‐like state in the K122 samples of type (i). The frequency dependence of their Tf follows a conventional power‐law divergence of critical slowing down <![CDATA[$\tau = \tau _{0} [T_{{\rm f}} (\nu )/T_{{\rm f}} (0)- 1]^{- z\nu '} $]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t13m" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with the critical exponent zν′ ≈ 10 and a relatively long characteristic time constant <![CDATA[$\tau _{0} \approx 6.9 \times 10^{- 11} \, {\rm s}$]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t18c" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> also supporting a CG behavior. The large value of the Sommerfeld coefficient obtained from SH measurements of these samples was related to the magnetic contribution from a CG. Samples from (ii) did not show a hysteresis behavior for χl(T) and M(B). Below some crossover temperature T* ≈ 50–80 K a power‐law dependence in the <![CDATA[$\chi _{{\rm l}} \, {\propto} \, T^{\lambda _{{\rm G}} - 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t17t" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />, with a non‐universal λG was observed, suggesting a quantum G‐like behavior. In this case χl and M(B) can be scaled using the scaling function <![CDATA[$M_{{\rm s}} (T, B) = B^{1- \lambda _{{\rm G}} } Y(\mu B/k_{{\rm b}} T)$]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t19x" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> with the scaling moment µ ∼ 3.5 µB. The same non‐universal exponent was found also in SH measurements, where the magnetic contribution <![CDATA[$C/T\, {\propto} \, T^{\lambda _{{\rm G}} - 1} $]]> <inline-graphic xlink:href="ark:/27927/pgg1v77t1bg" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />.